2000
DOI: 10.1046/j.1365-2141.2000.02312.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of fusariosis in patients with haematological diseases

Abstract: Fusariosis has been considered an emerging infection in patients with haematological malignancies. In a multicentre retrospective study on filamentous fungi infections in patients with haematological diseases over a period of 10 years in Italy, fusariosis was documented in six patients from two of the 14 centres with a 0.06% incidence in acute leukaemia. A literature search yielded 177 cases of Fusarium infections in haematological diseases and acute leukaemia accounted for 71% of the underlying conditions. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 36 publications
0
51
1
2
Order By: Relevance
“…However, there are two agriculturally significant F. oxysporum forms that are considered winter pathogens (9,17). Moreover, in Israel, fusarial infections are unrelated to rain and wind, in contrast to previous reports from other countries (3,10,30), since Israeli summers are rainless and hot (around 30°C). It is conceivable that the humidity, which is high in the coastal plain in the summer (55 to 70%) and low in the mountains (40 to 55%) (4), may partly explain the differences between these regions, as presented by more cases per 1,000 admissions in Sheba Medical Center, which is located in the coastal plain, than in the Hadassah University Hospital, located in the mountains of Jerusalem.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…However, there are two agriculturally significant F. oxysporum forms that are considered winter pathogens (9,17). Moreover, in Israel, fusarial infections are unrelated to rain and wind, in contrast to previous reports from other countries (3,10,30), since Israeli summers are rainless and hot (around 30°C). It is conceivable that the humidity, which is high in the coastal plain in the summer (55 to 70%) and low in the mountains (40 to 55%) (4), may partly explain the differences between these regions, as presented by more cases per 1,000 admissions in Sheba Medical Center, which is located in the coastal plain, than in the Hadassah University Hospital, located in the mountains of Jerusalem.…”
Section: Discussioncontrasting
confidence: 47%
“…The infection is most prevalent in autumn in France (16) and in summer in Texas and Italy (3,10,30). In Israel, the highest incidence of Fusarium species isolation was in the summer, particularly among patients from rural areas, and was associated with ocular and respiratory tract infections (6,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary IA is the most common cause of pneumoniarelated mortality in allogeneic SCT recipients and patients with leukemia [Kontoyiannis et al 2010]. A prospective US study of 234 SCT recipients reported that IA was the most frequent IFI (59.2%), followed by IC (24.8%) [Girmenia et al 2000;Pagano et al 2006].…”
Section: Epidemiology Of Invasive Fungal Infectionsmentioning
confidence: 99%